Tensile Strength and Thermal Properties of Polypropylene/Nano-Bentonite Composites with Maleic Anhydride Coupling Agent - Fitria Ika Aryanti; Teguh Budi Santoso (Jurnal Teknologi dan Manajemen, 2024)
Polypropylene is the most widely used polymer material in the automotive industry due to its properties such as good rigidity, high melting point, chemical resistance, and easy processability. Polypropylene is usually added with a filler, namely bentonite, to make polypropylene which has better mechanical and thermal properties. The coupling agent is added to improve the adhesion of the matrix with the surface so that the composite component has better durability. To improve the ability of the filler material, bentonite is converted into nanoparticles. Bentonite nanoparticles are expected to have better mechanical, thermal, electrical, and optical properties than particles with micro or macro sizes due to their large surface area. Based on the description above, it is necessary to study the effect of using bentonite nanoparticles with a coupling agent in the form of Maleic Anhydride-g-PP (MAPP) on the tensile strength and thermal properties of polypropylene composites. The variables of this study are the composition variation (weight %) of polypropylene, coupling agent (MAPP), and bentonite nanoparticles of 100:0:0, 95:0:5, 90:5:5, 85:5:10, 92:3:5, and 87:3:10. The method used in this study uses a twin-screw extruder tool with a temperature of 190°C and then tested regarding its tensile strength and thermal properties. The results showed that the addition of nano-bentonite tends to cause an increase in the decomposition temperature of the sample but does not increase the tensile strength of the composite, so it only functions as a polymer composite filler. While based on Differential Scanning Calorimetry (DSC) testing, the enthalpy value decreases with increasing concentration of coupling agent.